2011
DOI: 10.3892/ol.2011.546
|View full text |Cite
|
Sign up to set email alerts
|

Serum IGFBP-3 is a more effective predictor than IGF-1 and IGF-2 for the development of hepatocellular carcinoma in patients with chronic HCV infection

Abstract: Abstract. Hepatocellular carcinoma (HCC) contributes to 14.8% of all cancer mortality in Egypt, which has a high prevalence of hepatitis C virus (HCV). We have previously shown alterations in the insulin-like growth factor-1 (IGF-1) receptor signalling pathway during experimental hepatocarcinogenesis. The aim of this study was to determine whether serum levels of IGF-1, IGF-2 and IGFBP-3 can be used to discriminate between HCC and the stages of hepatic dysfunction in patients with liver cirrhosis assessed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 46 publications
3
32
1
Order By: Relevance
“…the obtained data were near those obtaind by Su et al, [26] who demonstrate that the development of HCC is accompanied by a significant reduction of serum IGF-I levels in comparison to healthy subjects which is also noted in chronic liver disease. To the opposite of our results, Aleem et al, [3] reported that the reduction of IGF-1 levels was statistically significant between cirrhosis and HCC patients. As regarding the decrease in IGF-1 in cirrhotic patients than healthy subjects many studies contribute this decrease to affection of liver parenchyma that reduce synthetic capability of damaged hepatocytes because hepatocytes are the main contributors of circulating IGF.The present study showed that there were significant positive correlations between IGF-1 level and total protein, albumin and MCP-1.…”
Section: Evaluation Of Taline-1 Mcp-1 and Igf-1 In Prediction Of Devcontrasting
confidence: 56%
See 1 more Smart Citation
“…the obtained data were near those obtaind by Su et al, [26] who demonstrate that the development of HCC is accompanied by a significant reduction of serum IGF-I levels in comparison to healthy subjects which is also noted in chronic liver disease. To the opposite of our results, Aleem et al, [3] reported that the reduction of IGF-1 levels was statistically significant between cirrhosis and HCC patients. As regarding the decrease in IGF-1 in cirrhotic patients than healthy subjects many studies contribute this decrease to affection of liver parenchyma that reduce synthetic capability of damaged hepatocytes because hepatocytes are the main contributors of circulating IGF.The present study showed that there were significant positive correlations between IGF-1 level and total protein, albumin and MCP-1.…”
Section: Evaluation Of Taline-1 Mcp-1 and Igf-1 In Prediction Of Devcontrasting
confidence: 56%
“…Most imaging techniques help to discover HCC after considerable time of onset of tumor. In most instances, oncologists depend on AFP as the commonest and feasible marker for assessing HCC in addition to imaging (3). However, AFP is not completely a reliable marker in early HCC diagnosis, prevention or therapy due to its low specificity and sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Egypt has a high prevalence of HCC; it is the second most cancer site among males after cancer bladder and seventh among females [2] . Such high incidence has been attributed to the high prevalence of hepatitis C virus (HCV) amongst Egyptians [3] .Based on histological characters, most HCCs can be easily identified on hematoxylin and eosin stained sections. However, some types of benign and malignant tumors may share the morphologic features.…”
mentioning
confidence: 99%
“…Egypt has a high prevalence of HCC; it is the second most cancer site among males after cancer bladder and seventh among females [2] . Such high incidence has been attributed to the high prevalence of hepatitis C virus (HCV) amongst Egyptians [3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation